LEARNING APP IN A SYSTEMATIC REVIEWING - Michael Olubunmi Odewumi; Isyaka Bello (IJIET (International Journal of Indonesian Education and Teaching), 2021)
The purpose of the study was to find out a systematic reviewing of apps for instruction in the context of creative arts in Nigeria Junior Secondary Schools. The study also investigated the influence of gender students’ taught with apps.  The quasi-experimental design, which is of the pre-test and post-test was used.  The research sample was drawn from two randomly selected secondary schools. One intact class in each sampled school was also randomly selected for the study. The students from the sampled class were further stratified along with gender boys and girls. The Learning App, Validated test, and Marking guide were the instruments.  Two hypotheses were tested using Analysis of Covariance and t-test. Findings indicated that students taught with apps performed significantly better than those taught without. It also revealed the gender of students was not a factor in the performance of students when they were taught using apps this was because there was no significant difference between the performance of male and female students. Based on these findings, it was recommended that the use of apps should be encouraged in teaching creativity in Nigeria schools.